Elevated monocyte chemotactic proteins 1, 2, and 3 in pulmonary alveolar proteinosis are associated with chemokine receptor suppression - Bonfield, Tracey L (Clinical immunology (Orlando, Fla.), 2005)
Pulmonary alveolar proteinosis (PAP) is a rare autoimmune lung disease characterized by abnormal surfactant accumulation within alveolar macrophages, and circulating auto-antibodies against granulocyte-macrophage colony stimulating factor (GM-CSF) resulting in functional GM-CSF deficiency. Monocyte/macrophage chemotactic protein-1 (MCP-1) is elevated in PAP, suggesting association with the pathophysiology. Because PAP has been associated with inflammatory pulmonary changes, we hypothesized that other MCP family chemokines would be present and that Chemokine Chemotaxis Receptor 2 (CCR2) would be elevated on PAP mononuclear cells. Here we show for the first time that MCP-2 and MCP-3, like MCP-1, are highly elevated in PAP. We also confirm that PAP alveolar macrophages and not epithelial cells produce MCP-1, and that MCP-1 from PAP lung has functional chemoattractant activity. Surprisingly, CCR2 expression is diminished in PAP lymphocytes and alveolar macrophages compared to controls. Further, MCP-1 from PAP lung suppresses CCR2 expression in vitro, suggesting that in PAP, MCP-1 participates in an autocrine regulatory network in vivo